Inhibition of chikungunya virus replication by hesperetin and naringenin - Ahmadi, A.; Hassandarvish, P.; Lani, R.; Yadollahi, P.; Jokar, A.; AbuBakar, Sazaly; Zandi, Keivan (Royal Society of Chemistry, 2016)
Chikungunya virus (CHIKV) is an emerging arbovirus, which has recently become globally important. In recent years, it has posed a progressive threat to humankind, causing the development of possibly life-threatening and incapacitating arthritis. Currently, there is no available effective antiviral drug for chikungunya infection. Thus, finding and developing lead compounds with anti-CHIKV activity that could be further developed into a practical treatment is urgently required. Several studies have reported the wide-ranging antiviral activities of flavanones; however, an inhibitory effect of selected compounds has yet to be shown against CHIKV. In this study, we investigated the antiviral properties of two types of flavanones, namely naringenin and hesperetin, against CHIKV in vitro replication. Our data have shown dose dependent inhibitory effects for naringenin and hesperetin against CHIKV intracellular replication using different assays, including the CHIKV replicon cell line, time-of-addition and virus yield assays. The antiviral activity of the compounds was further investigated by the evaluation of CHIKV protein expression using a quantitative immunofluorescence assay and western blotting. In brief, these compounds presented significant antiviral activity against CHIKV, reducing both the CHIKV replication efficiency and down-regulating the production of viral proteins involved in replication. Naringenin with IC50 = 6.818 μM (SI = 80.27) and hesperetin with IC50 = 8.500 μM (SI = 23.34) inhibited the post entry stages of CHIKV replication activity. In conclusion, the obtained data from the current study suggest that naringenin and hesperetin could be potential candidates to be developed further as anti-CHIKV therapeutic agents.